MOLECULAR SIMULATION OF HUMIC SUBSTANCE-CA-MONTMORILLONITE COMPLEXES - Sutton R.; Sposito G. (My University, 2006)
An understanding of the processes that lead to long-term stabilization of organic matter in soils is essential to the effective implementation of strategies designed to mitigate CO2 loss from the soil carbon reservoir in temperate climatic zones. Decomposition studies indicate that montmorillonite, a smectite that often forms with interlayers rich in Ca2+, greatly retards the microbial mineralization of soil organic matter. We performed a series of atomistic simulations designed to identify favorable molecular-scale organo-mineral interactions within nanoscale, hydrated complexes consisting of a humic substance and Ca-montmorillonite. Both protonated and Ca-saturated forms of the model humic molecule, representing acidic and circumneutral solution conditions, respectively, were studied within the hydrated interlayer region of a rigid-atom model of Ca-montmorillonite. The protonated humic substance formed direct hydrophobic and hydrogen bonding (H-bonding) interactions with the clay mineral. A few polar organic groups adsorbed via water bridging interactions. The Ca-saturated humic substance adsorbed via numerous cation bridges, less numerous water bridges, and indirect H-bonding interactions mediated by water molecules. Application of molecular modeling techniques to this complex organo-mineral system thus allowed identification of interactions favorable to carbon sequestration under both acidic and circumneutral conditions.
Keywords: CLAY MINERAL; HUMIC ACID; MOLECULAR ANALYSIS; MONTMORILLONITE; SMECTITE; SOIL CARBON; SOIL ORGANIC MATTER